Gezondheid : 75 jaar Nationaal Verbond van Socialistische Mutualiteiten 1913-1988 - Vermote, Michel; Claes, Willy; Balthazar, Herman (Gent: Amsab, 1988)
"Michel Vermote ; Voorzitter Willy Claes ; Prof. dr. Herman Balthazar"